Optical quality assessment of a motorway route - Oginskas, Rolandas; Bertulienė, Lina; Juknevičiūtė-Žilinskienė, Lina; Gintalas, Vilimas; Lenkauskas, Andrius (International Conference “Environmental Engineering”, 2017)
A roads and highways are a complex structures consisting of different geometric and structural elements. Some of those elements influence the driving comfort, speed and traffic safety whereas others contribute to motorway durability and its proper function during different seasons of a year. The development of motorway const ruction or reconstruction designs either relies or is about to rely on the principles of spatial design of a motorway route. The application of the said principles improves optical quality of the route and leads to a correct comprehension of the motorway concerned. Nevertheless, the global as well as the European and the Lithuanian experience witnesses the cases of the emergence of unavoidable optical deformations in the solutions of motorway route design and the reason for that could be an unavailability of clear requirements set forth in the relevant standard documents in force in regard to coordination between the horizontal alignment and the vertical alignment of motorway elements. The missing coordination between the solutions of horizontal alignment and vertical alignment of the motorway turns to be the cause for lower levels of driving comfort and traffic safety, as an adequate prevision of the current situation driving such a motorway cannot always be possible. A parameter known as Curvature Change Rate of single curve (CCRs) is applied by numerous countries to assess the quality level of horizontal alignment of the existing or design motorway route. The present article presents a variation of the vertical alignment of a motorways in Lithuania relying on Curvature Change Rate of vertical curve (CCRv) parameter.
Keywords: road safety; road design; geometric design; horizontal alignment; vertical alignment